Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jmv.25680
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity as predictor of immune reconstitution among Malaysian HIV‐positive patients treated with highly active antiretroviral therapy

Abstract: The impact of sociodemographic and clinical factors on immune recovery and viral load suppression among HIV-1 positive patients treated with HAART particularly in Malaysia is largely unknown. This cross-sectional study enrolled 170 HIV-1-infected individuals of three major ethnicities who attended three HIV outpatient clinics in Malaysia. Questionnaire was used to obtain sociodemographic data while CD4 count and viral load data were gathered from hospital's record. Multiple factors were assessed for their pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Morbidity among the females of Malaysia peaked in young adults and was significantly lower than that among men, possibly because more than two-thirds of new cases in the country were among men aged 20−39 years old who had sex with other men; worryingly, this age group is the most productive. 37 From 1990 to 2019, the major risk factor for HIV/AIDS in Malaysia changed from drug use to unsafe sex, possibly due to the country's previous efforts to address HIV transmission among intravenous drug users through its Needle and Syringe Programme. 38 There is significant diversity across the Asia-Pacific region, and as such, the response to the AIDS epidemic must be tailored to individuals from nations with a wide range of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity among the females of Malaysia peaked in young adults and was significantly lower than that among men, possibly because more than two-thirds of new cases in the country were among men aged 20−39 years old who had sex with other men; worryingly, this age group is the most productive. 37 From 1990 to 2019, the major risk factor for HIV/AIDS in Malaysia changed from drug use to unsafe sex, possibly due to the country's previous efforts to address HIV transmission among intravenous drug users through its Needle and Syringe Programme. 38 There is significant diversity across the Asia-Pacific region, and as such, the response to the AIDS epidemic must be tailored to individuals from nations with a wide range of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11–13 ] Some demographic characteristics (age, gender, and ethnicity) may also be associated with the immune recovery in some studies. [ 14,15 ] Moreover, available studies have revealed the immune proliferation, senescence, exhaustion, and percentages of regulatory T cells (Tregs) may also reflect the immune recovery. [ 16,17 ] The nutritional status, [ 18 ] such as body mass index (BMI), [ 19 ] hemoglobin (HB), [ 20 ] and other parameters, [ 18 ] has been widely used for the assessment of prognosis of HIV‐infected patients, but their roles in the assessment of immune recovery are still controversial.…”
Section: Introductionmentioning
confidence: 99%